Hepatocellular carcinoma in children and young patients with chronic HBV infection and the usefulness of alpha‐fetoprotein assessment. (17th October 2016) - Tajiri, Hitoshi; Takano, Tomoko; Tanaka, Hideo; Ushijima, Kosuke; Inui, Ayano; Miyoshi, Yoko; Ozono, Keiichi; Abukawa, Daiki; Endo, Takeshi; Brooks, Stephen; Tanaka, Yasuhito
Abstract: The aims of the study were to elucidate the clinical characteristics of patients who developed hepatocellular carcinoma (HCC) related to persistent HBV infection since childhood and to investigate usefulness of assessing alpha‐fetoprotein (AFP) in this population. A nationwide multicenter survey of children with chronic HBV infection was performed. Among 548 patients, 15 patients developed HCC at the median age of 15 years (range 9–36), including 13 males and 2 females. A case–control comparison showed that HBeAg seroconversion and liver cirrhosis were associated with the occurrence of HCC. Of the 15 HCC patients, 5 were treated with interferon and none of them responded to interferon therapy as compared with 12 of the 17 responders in the control group. Of the 15 patients, 10 died and 9 of the 10 who died never visited any medical facilities until diagnosis of HCC, while the remaining 5 surviving patients never stopped their clinic visits. The usefulness of AFP assessment was shown by the findings that AFP levels were elevated in all HCC cases, that elevations in AFP levels were detected prior to the diagnosis in the surviving patients, and that sensitivity of AFP as a diagnostic test for HCC was very high among 40 patients including our 14 and an additional 26 collected from the literature. HBeAg seroconversion and liver cirrhosis are associated with the occurrence of HCC. Regular measurement of AFP might be helpful to watch for the occurrence of HCC when following children and young patients with chronic HBV infection since childhood Abstract : Both HBeAg seroconversion and liver cirrhosis are associated with the occurrence of hepatocellular carcinoma (HCC). Regular measurement of alpha‐fetoprotein (AFP) might be useful in early diagnosis of HCC among children with chronic HBV infection.